Modular dual-mobility cups using ceramic liners: an original solution for selected indications?. Issue 2 (December 2020) - D'Apolito, Rocco; Bandettini, Guido; Jacquot, Filippo Maria Piana; Zagra, Luigi
Background: Dual mobility (DM) has been shown to improve stability both in primary and revision total hip arthroplasty (THA) and is increasingly used in patients at high risk of dislocation and in the treatment of THA instability. The introduction of modular liners has helped to overcome some of the limitations of monoblock DM cups. In this context, the use of a ceramic liner would avoid the conventional cobalt-chromium liner in the titanium shell, which can be problematic in some situations. The aim of this paper is to report the outcomes of a consecutive series of patients undergoing revision THA using a modular DM cup with a ceramic liner instead of the conventional metal one, and to clarify the rationale for this currently "off-label" use. Patients and methods: This is a retrospective series of patients who received this new DM bearing in a single institution. Patients were followed up clinically and radiologically at 1 month, 3 months, 6 months and yearly thereafter. Results: 5 patients received the ceramic liner in the study period (2014–2019). The indications were instability or high risk of dislocation in ceramic liner fracture and ARMD with soft tissue damage after MoM THA. The mean age at surgery was 74 (63–82) years, the mean follow-up was 36 (12–72) months. No dislocation occurred, and no adverse events related to the implant were recorded. Conclusions: The use of a ceramic liner in a modular DM cup offers several advantages in selected patients, and the results of our cohort are encouraging. However, caution is needed in introducing this new bearing because knowledge is currently limited. Further studies on a larger number of patients and with longer follow-ups are needed to confirm these findings and before widespread use of the device.